Model Peningkatan Kinerja Melalui Disiplin Kerja Sebagai Intervening pada Pegawai Dinas Pendidikan Kota Padang - Yulina Eliza; Yass Andria; Evi Adriani (Universitas Batanghari, 2022)
Performance is a picture of the results achieved in the implementation of a policy realized through the strategic planning of an organization including the goals, goals, vision, and mission of the organization. The performance of employees of the Regional Device Organization (KOPD) of the Padang City Education Office is still not optimal, where the placement of employees is not by the competencies needed by the organization. Employee absenteeism increased by 2-5% per month due to several things such as delays in employees entering the office, employees applying for permission for family affairs and employees who do not give news or without information. The purpose of this study was to test variables that affect employee performance using work discipline intervening variables with 101 samples at the Padang City Education Office. The results of the study prove that: 1) employee discipline is positively and significantly influenced by work competence; 2) employee discipline is positively and significantly influenced by work culture; 3) employee performance is positively and significantly affected by work competence; 4) employee performance is positively and significantly affected by the work culture; 5) Employee performance is positively and significantly affected by work discipline; 6) Employee performance is positively and significantly affected by work competence with work discipline as an intervening variable; 7) Employee performance is positively and significantly influenced by work culture with work disciplines such as intervening variables in the Padang City Education Office.